Concept of Buying and Selling Transactions UsingQuick Response Indonesian Standard Perspective of DSN MUI Fatwa No: 116/DSN-MUI/IX/2017 Concerning Sharia Electronic Money - Syifaun Nada (JIQSI : Jurnal Ilmu Al Qur'an dan Studi Islam, 2023)
The payment system cannot be separated from the development of money, starting from cash payments to non-cash payments. Bank Indonesia launched the Quick Response (QR Code) standard as stated in Board of Governors Regulation Number 21/18/PADG/2019 concerning Implementation of the National Quick Response Code Standard for Payments. This QR Code is a payment via a server-based electronic money application, electronic wallet, or mobile banking called QR Code Indonesian Standard (QRIS). When the digital payment applications used by consumers are different, the shop (merchant) only needs to provide 1 QR code. QRIS, like electronic money, offers a lot of comfort and convenience. However, apart from having many benefits and advantages, it raises pros and cons among the public. Some parties doubt the security and effectiveness of this payment system and this system still requires socialization regarding the procedures for its use. Buying and selling using QRIS to Merchants is the same as a general sale and purchase agreement, namely a contract between two parties where the first party hands over the goods and the second party hands over compensation, either in the form of money or goods. However, the implementation of MDR is only determined by one party, namely Bank Indonesia without agreement or an element of willingness by the merchant, resulting in coercion (AlIkrah), so the use of QRIS in electronic transactions does not meet legal requirements and according to Hanafiyah scholars, the contract is false. This is because QRIS can be used if electronic money is available in an application. So the use of electronic money has been regulated as a means of payment by following the provisions contained in the Fatwa of the National Sharia Council of the Indonesian Ulema Council No: 116/DSNMUI/IX/20I7 concerning Sharia Electronic Money. From a sharia law perspective, electronic money or e-money is permitted based on the many benefits contained in it.